Landslide risk assessment - Lee, E. Mark; Jones, David K. C. (ICE Publishing, 2014)
There has been a gradual shift away from simply relying on engineering solutions to individual landslide problems, to the use of a variety of strategies to manage the problems over a broad area. This book addresses these developments and provides a multidisciplinary perspective on landslide management.